해외직접투자가 기업의 재무성과에 미치는 영향: 한국의 중소기업과 대기업 비교를 중심으로 - 맹선배(Maeng, Seon Bae); 김순철(Kim, Soon Choul) (벤처창업연구, 2023)
This study aimed to empirically analyze the effect of Korean companies' FDI(Foreign Direct Investment) on their financial performances, particularly divided into profitability, stability, growth and activity, while comparing distinct financial performances between SMEs(small and medium-sized enterprises) and large enterprises whose corporate attributes are different from each other. As research subjects, this study selected FDI Korean companies from the directory of oversea-expanded companies of KOTRA(Korea Trade-Investment Promotion Agency) and used financial data from a total of 409 companies(136 SMEs and 273 large enterprises) with complete financial data for the first five years after the initial investment out of all the financial data from 1990 to 2021. The analysis results can be summarized as follows; In the profitability sector, FDI had positive effects on ROA(Return on Assets) and ROS(Return on Sales) of SMEs, while having negative effects on those of large enterprises to the contrary. In the stability sector, FDI had no statistical significance for SMEs, while having significantly negative effect on LEV(Debt to Equity Ratio) of large enterprises. In the growth sector, FDI had significantly negative effect on AGR(Asset Growth) of SMEs, but showed no significant results for large enterprises. In the activity sector, FDI showed no statistical significance for SMEs, while having positive effects on ATR(Asset Turnover Ratio) and FATA(Fixed Asset Turnover Ratio) of large enterprises. In conclusion, it was found that when having made FDI, SMEs and large enterprises showed different financial performances from each other in terms of profitability, stability, growth and activity. 본 연구는 한국기업의 해외직접투자가 재무성과에 미치는 영향을 수익성, 안정성, 성장성, 활동성 부문으로 구분하여 실증 분석하였고, 기업 속성이 다른 중소기업과 대기업에서 각각 특징적 재무성과가 있는지 비교하였다. 해외직접투자 기업은'한국무역투자진흥공사'해외진출기업 Directory에서 선정하였고,'Fn Guide'를 활용하여 1990년부터 2021년까지의 재무자료 중 최초 투자 후 5년간의 재무자료가 완벽한 총 409개 기업(중소기업 136개, 대기업 273개)의 재무자료를 사용하였다. 분석 결과, 수익성부문에서 중소기업은 총자산영업이익률(ROA), 총매출액영업이익률(ROS)에 각각 정(+), 대기업은 각각 부(-)의 영향이 나타나 결과가 달랐다. 안정성부문에서 중소기업은 통계적 유의성이 없었으나 대기업은 부채비율(LEV)에 유의한 부(-)의 영향을 보였다. 성장성부문에서 중소기업은 총자산증가율(AGR)에 유의한 부(-)의 영향이 나타났고, 대기업은 유의한 결과가 없었다. 활동성부문에서 중소기업은 통계적 유의성이 없었으나 대기업은 총자산회전율(ATR), 고정자산회전율(FATR)에 정(+)의 영향이 있었다. 결론적으로 중소기업과 대기업의 해외직접투자는 수익성과 안정성, 성장성, 활동성의 재무성과가 서로 다르게 나타났다.